Peranan Mahasiswi KKN dalam Gerakan Menutup Aurat (Gemar) di Desa Allaere Kecamatan Tanralili Kabupaten Maros - Rosmita Rosmita; Muttazimah Muttazimah (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
Community service which includes efforts to improve the quality of human resources in religious aspects and as a form of concern in developing society. The methods used in implementing community service through real work lectures are: Observation, Interviews, Preparation of work program workshops (Village Seminars). After the analysis is carried out, a work program is prepared that is appropriate and needed by the community. GEMAR Movement to Cover Private Parts is one of the work programs where this activity is specifically for Muslim women in Allaere village with the aim of activities to build awareness of the entire community about the importance of a Muslim woman covering her private parts. This program has been running well and has shown initial results in accordance with the KKN objectives that have been planned, namely inviting 44 Muslim women as participants and forming 4 intensive study groups.